PENGARUH MOTIVASI BERPRESTASI DAN KOMUNIKASI KERJA TERHADAP PROFESIONALISME GURU SD SE-KECAMATAN NGALIYAN, KOTA SEMARANG - Sri Susilaningsih (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
The most strategic and systematic component in improving the quality of education is teacher component, especially related with the effort in showing professional ability. In this case the teacher really expected to be able to manage the other components in one system. The population in this research are the whole level of achievement motivation and works of communication of elementary school teacher in Ngaliyan subdistrict Semarang which number are 106 persons spread in 14 elementary school i.e. SDN Kalipancur 1, SDN Kalipancur 2, SDN Purwoyoso 1, SDN Purwoyoso 2, SDN Purwoyoso 3, SDN Purwoyoso 4, SDN Wates 1, SDN Wates 2, SDN wates 3, SDN Tambakaji 1, SDN Tambakaji 2, SDN Koalisi (Ngaliyan Campus), SDN Wonosari 1, and SDN Wonosari 2. Sample determination using random sampling and simple random sampling. Then the data processed quantitatively using SPSS 12 version for Windows 2000 include descriptive analysis, simple correlative and regression. The result of first hypothesis experiment is equation Y = 1,486 + 0,631 X1. So that the hypothesis that mention there is a positive and significant influence between achievement motivation and teacher professionalism is received. The value of R2 is 0,369 showing that motivation achievement gives contribution for 36,9% to the form of teacher professionalism. Achievement motivation is very important for the successful of teacher’s effort because it is strong encouragement and appear in oneself consciously or unconsciously to do action for certain purposes in order to avoid the fail. So the higher teacher’s achievement motivation so more and more teacher professionalism the opposite is lower teacher’s achievement motivation so the professionalism becoming lower. The result of second test hypothesis is the equation Y = 1,487 – 0,017 X1 0,0614 X2. With this hypothesis expectation mention that there is positive and significant influence between teacher’s professionalism and works of communication is received. The value of R2 IS 0,373 show that communication gives 37,3% contribution to the forming of teacher professionalism. It shows that more effective works of communication, so that teacher’s professionalism becoming higher. Based on the result of experiment concluded that teacher professionalism influenced by achievement motivation and works of communication. The result of this experiment is empirical evidence that achievement motivation and works of communication influenced elementary school teacher’s professionalism in Ngaliyan subdistrict Semarang. Therefore, it needs an effort of improve teacher professionalism as needed to improve achievement and the existence of communication.